Analysis of runoff and sediment evolution and attribution in the source regions of the Yangtze and Yellow Rivers - Shu Xu; Tianling Qin; Xizhi Lv; Jie Lu; Jianming Feng; Haoyue Gao; Hanxiao Liu; Yuhui Yang (Journal of Hydrology: Regional Studies)
Study region: The source regions of the Yangtze and Yellow Rivers Study focus: The purpose of this study is to analyze the latest evolution trends of runoff and sediment load in the source areas of the Yangtze and Yellow Rivers, quantitatively attribute the evolution drivers of runoff and sediment load in the region by Structural Equation Model, and predict the future evolution trends. New hydrological insights for the region: The results showed that from 2000 to 2020, the runoff of the source region Yangtze and Yellow Rivers increased at rates of 2.56 × 108 m3/a and 5.98 × 108 m3/a, and the sediment load increased at rates of 33.24 × 104t/a and 36.82 × 104t/a, respectively. Attribution analysis found precipitation has the greatest impact on runoff and sediment changes. Although snowmelt is also an important factor, its contribution is still relatively small compared to precipitation. The vegetation in the region did not significantly reduce sediment under freeze-thaw conditions. The prediction results show that the runoff and sediment load in the region will continue to increase in the future. From 2025–2098, the runoff in the source area of the Yangtze River and the source area of the Yellow River will increase at a rate of 0.21–1.11 × 108 m3/a and 0.14–0.68 × 108 m3/a, and the sediment load will increase at a rate of 1.62–6.12 × 105t/a and 2.44–5.78 × 105t/a, respectively.